Utilization of colorectal cancer screening tests: a systematic review and time trend analysis of nationally representative data - Ganiyu, Idris Olayiwola; Cardoso, Rafael; Hoffmeister, Michael; Brenner, Hermann (EClinicalMedicine, 2024)
Background - The substantial and increasing global burden of colorectal cancer (CRC) underscores the imperative to enhance implementation and utilization of effective CRC screening offers. Therefore, we examined the lifetime and up-to-date use of CRC screening tests across various countries, and described utilization trends over time. - Methods - We conducted a systematic review on the extent and recent trends of utilization of CRC screening tests among people 45 years or older in different countries around the globe. PubMed/Medline, Web of Science, and Embase electronic databases were screened for eligible studies from inception to June 30, 2024. The study protocol was registered with international prospective register of systematic reviews (PROSPERO) (CRD42023391344). - Findings - A total of 50 studies, based on nationally-representative data, were finally included - 27 from the United States (US) and 23 from other countries. The overall utilization of CRC screening has steadily increased over time in many countries, reaching 74.9% in Denmark in 2018-2020, 64% in Korea in 2020, and 72% in the US in 2021. Nevertheless, the utilization rates remain far below the national or continental targets in most countries. In contrast to European and Asian countries, where screening was predominantly fecal test-based, the approach in the US was primarily driven by colonoscopy, and the uptake of fecal tests and sigmoidoscopy gradually declined in the past two decades. - Interpretation - Despite ongoing progress in CRC screening offers and utilization, there remains large potential for enhanced roll-out and utilization of effective CRC screening programs for enhanced control of CRC incidence and mortality in the years ahead. - Funding - There was no funding source for this study.